Leaf cuticle anatomy and the ultrastructure of Ginkgoites Ticoensis Archang. from the Aptian of Patagonia - del Fueyo, Georgina Marisa (2013)
The leaf cuticle of the Ginkgoites ticoensis Archang. type material from the Aptian Anfiteatro de Tico ́ Formation in Patagonia, Argentina, is fully characterized with additional scanning and transmission electron microscopic observations. Many new anatomical and ultrastructural cuticular features are identified in the four-lobed leaf of G. ticoensis: the leaf shows a hypostomatic and papillate laminae, straight and pitted anticlinal and granulate periclinal walls, actinocytic stomata with between five and seven papillate, striate subsidiary cells, and guard cells with anticlinal smooth walls. The TEM studies on ordinary epidermal cells, papillae, subsidiary cells, and guard cells reveal general ultrastructural features of Ginkgoaceae: an outer polylamellate layer A made with A1 and a granular inner layer A2; A1 with an upper part A1U with continuous and straight translucent lamellae; a lower part A1L with significantly disrupted and waving translucent lamellae; and the fibrillar cuticular layer B1 as the innermost part. Ten ultrastructural characters are detailed and ranked by the use of confidence intervals based on 30 statistical measurements. A three- dimensional reconstruction of the cuticle is also provided. Because of the anatomical and ultrastructural fine details shown in the G. ticoensis cuticle, new elements are given to suggest its probable family affinity and to enhance the specificities of Ginkgo and Ginkgoites.